Homeostasis Cairan Tubuh pada Anjing dan Kucing - Anthara, I Made Suma; Suartha, I Nyoman (Buletin Veteriner Udayana, 2012)
The body’s fluid is compartmentalized into two major divisions: the intracellular fluid(ICF) and the extracellular fluid (ECF). The ECF which is also called the internalenvironment of the body is in constant motion throughout the body. The ECF contains largeamounts of sodium chloride, and bicarbonate. The ICF contains large amounts potassium andphosphate. Transported of water and nutrient through cell membrane occurs by diffusion,osmosis and sodium-potassium pumps. The homeostasis of body fluid is maintains bykidney.
Keywords: homeostasis, fluid, electrolyte, kidney